UTILIZATION OF THE KRUENG ACEH RIVER BEDROOM POST SETUP ACCORDING TO AD-DAULAH MILK PERSPECTIVE - Muslem Muslem (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
The Krueng Aceh Watershed (DAS) is one of the state assets managed by the Sumatra-I River Basin, so it is widely used by the surrounding community to meet the needs of life on the banks of the Krueng Aceh river. Management of land along the river is the main goal to anticipate in reducing the potential for flooding. Therefore, the author wants to examine in detail the process of riverbank land use carried out by the Krueng Barona Jaya community, forms of riverbank land use and their use according to the perspective of milk al-daulah. The method used in this study is a qualitative method through primary data obtained by direct field research using interview, observation, and documentation techniques. The results of this study indicate that the process of using land along the Krueng Aceh river by the Krueng Baroena Jaya community after the Krueng Aceh river arrangement refers to the past law, namely customary law, so there is no administrative data recorded as evidence that they have permission to use the riverbanks. The forms of land use along the Krueng Aceh river that are carried out by the Krueng Barona Jaya community on riverbank land are by constructing buildings, opening culinary stalls, plantation land and livestock land. In terms of utilization carried out by the people of Krueng Barona Jaya in terms of buildings, the licensing process, and the forms of utilization, it is a violation that is contrary to the Regulation of the Minister of PUPR of the Republic of Indonesia Number 28/PRT/M/2015 Article 22 concerning Determination of River Border Lines and the concept of milk al-daula. Therefore, the government must immediately bring back the land along the Krueng Aceh banks so that its utilization is in accordance with the applicable provisions.